Questioning the Validity of the New York Convention 1958 on Recognition and Enforcement of Foreign Arbitral Awards in Indonesia - Roosdiono, Anangga W.; Taqwa, Muhamad Dzadit (Pandecta Research Law Journal, 2024)
This article questions the legal validity of the New York Convention of 1958 ("NYC 1958") on the recognition and enforcement of foreign arbitral awards. A critical review is conducted based on the principle of lex posterior derogat lex priori when the provisions of NYC 1958 are compared with Articles 65 to 69 concerning the enforcement of international arbitral awards in Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution (Law 30/1999), which emerged approximately 18 years after (posteriori to) the ratification of NYC 1958 through Presidential Decree No. 34 of 1981. There appears to be—from the perspective of legal scholars—a paradigmatic difference between the two, namely that NYC 1958 places greater value on foreign arbitral awards, while Law 30/1999 is less appreciative of them, leading to the presumption that Law 30/1999 nullifies the legal validity of NYC 1958. Can this perception be justified? The answer to this question shapes the judicial paradigm when faced with applications for the recognition and enforcement of foreign arbitral awards. This article, doctrinally, compares and links the paradigmatic nuances between NYC 1958 and Law 30/1999 with regard to the recognition and enforcement of foreign arbitral awards by closely examining the textual provisions of each regulation.